KORELASI TEORI BELAJAR DENGAN TEKNOLOGI PENDIDIKAN - Arifin, Saiful; Rahayu, Puji; Ardhianto, Putut; Wargiani, Sri; Ziyanatu Zahro, Ulya (Social Science Academic, 2023)
The presence of technology in human life gives a new color both in everyday life, work-life, and the world of education. This paper wants to examine the relationship between learning theory and educational technology by using descriptive qualitative research with a literature study approach. The method used in conducting this research is using a literature study approach where the researcher collects data relevant to the topic being researched. The results of this study indicate that 1) the impact of the revolution itself affects the world of education, 2) technology is an element of the industrial revolution era that cannot be stopped, 3) technology in education gives a new face to the existing learning process in the existing curriculum and learning tools, where educational actors compete and try to create a collaborative learning cycle between learning theory and technology-based education. It can be concluded that learning theory and educational technology correlate with the application of learning carried out by teachers and students, where learning theory and educational technology are necessary units in the learning cycle so that the atmosphere of the students remains focused on the learning taught by the teacher